Dietary fiber intake associated with reduced risk of epithelial ovarian cancer in southern Chinese women - Tang, L.; Lee, Andy; Su, D.; Binns, C. (2015)
Objective: Ovarian cancer is the third most common gynecological malignancy and the eighth leading cause of cancer-related deaths among women worldwide. The present study aimed to investigate the association between dietary fiber intake and the risk of epithelial ovarian cancer in southern Chinese women. Methods: A case-control study was undertaken in Guangzhou, Guangdong Province, between 2006 and 2008. Participants were 500 incident ovarian cancer patients and 500 hospital-based controls. Information on habitual foods consumption was obtained by face-to-face interview, from which dietary fiber intakes were estimated using the Chinese food composition tables. Unconditional logistic regression analyses were performed to assess the association between dietary fiber intake and the ovarian cancer risk. Results: The ovarian cancer patients reported lower intake levels of total dietary fiber and fiber derived from vegetables, fruits and cereals than those of controls. Overall, regular intake of fiber was inversely associated with the ovarian cancer risk, the adjusted odds ratio being 0.09 (95% confidence interval 0.05 to 0.14) for the highest (> 21.9 g) versus the lowest (< 16.5 g) tertile of daily intake, with a significant dose-response relationship (p < 0.001). Similar reduction in risk was also apparent for high intake level of vegetable fiber, but to a lesser extent for fruit fiber and cereal fiber. Conclusion: Habitual intake of dietary fiber was inversely associated with the incidence of epithelial ovarian cancer in southern Chinese women.